Acoustic density of the sclera of keratoconus eyes and its clinical significance - E. P. Tarutta; A. T. Khandzhyan; T. N. Kiseleva; S. V. Milash; A. V. Ivanova; O. V. Guryanova; G. A. Markosyan; A. N. Bedretdinov; K. A. Ramazanova (Российский офтальмологический журнал)
Purpose: to assess the biophysical properties of the sclera by measuring its acoustic density in keratoconus, highly myopic, and healthy eyes. Material and methods. We examined 34 patients (67 eyes) aged 15–45 with keratoconus of various stages, 15 patients (30 eyes) aged 17–28 with high myopia and 15 people (30 eyes) aged 28–37 without ophthalmic pathology. The acoustic density of the sclera (ADS) was measured on the Voluson Е8 ultrasound device (GE Healthcare, USA) in the posterior eye pole (ADS-1) and in the equatorial area (ADS-2). The axial length (AL) of the eye, corneal thickness (CT), anterior chamber depth (ACD), and lens thickness (LT) were determined using Galilei G6 (Ziemer Group, Switzerland). The vitreal chamber depth (VCD) was calculated according to the formula: VCD = AL – СT – ACD – LT. Results. In keratoconus patients, the average ADS-1 value was 242.5 ± 7.4 conventional units (CU), ADS-2 averaged 234.1 ± 12.1 CU, AL was 24.6±1.1 mm long, and VCD was 17.1 ± 0.4 mm. In high myopia group, the average value proved to be significantly lower: ADS-1 was 210.3 ± 15.7 CU, ADS-2 — 201.2 ± 11,2 CU, while AL and VCD were higher: resp. 27.0 ± 0.7 mm and 19.2 ± 0.5 mm (p < 0,05). In the control group (healthy eyes), ADS-1 was 247.5 ± 2.8 and ADS-2 was 238.1 ± 0.6 CU, which practically showed no difference to the keratoconus group (p > 0.05). AL was 23.7 ± 0.6 mm, and VCD was 16.0 ± 0.6 mm. An insignificant tendency toward ADS drop in keratoconus eyes with AL over 25.0 mm was observed. Probably, we are dealing here with a combination of keratoconus with axial myopia. Conclusion. The acoustic density of the sclera of keratoconus patients approaches the respective parameter of healthy eyes and is significantly higher than that of highly myopic eyes. The analysis of acoustic density of the sclera and vitreal chamber depth may be considered as a method of additional differential diagnostics of keratoconus and congenital myopia with high corneal refraction and astigmatism.